Lipopolysaccharide-induced impairment of nitric oxide-mediated vasorelaxation and protective effects of nitric oxide synthesis inhibitors in isolated rat mesenteric arteries - Miike, Tomohiro; Kanda, Mamoru; Kunishiro, Kazuyoshi; Shirahase, Hiroaki (Arzneimittelforschung, 2010)
Isolated rat mesenteric arteries were in-cubated with lipopolysaccharide (LPS) for 6 h and then mounted in an organ bath to investigate their responses to various relaxants. Exposure to LPS moderately reduced acetylcholine (ACh)-induced endothelium-dependent relaxation (EDR),and markedly reduced sodium nitroprusside (SNP)-induced endothelium-independent relaxation (EIR). It did not affect ACh-induced EDR under treatment with a nitric oxide synthase (NOS) inhibitor,which is mediated by an endothelium-derived hyperpolarizing factor (EDHF),and forskolin-induced EIR. N-(3-(Amino-methyl)benzyl)acetamidine (1400 W), an inducible nitric oxide synthase (iNOS) inhibitor, actinomycin D, an RNA polymer-ase inhibitor, cycloheximide, a protein synthesis inhibitor, and dexamethazone reduced the nitric oxide (NO) production and reversed the reduced ACh-induced EDR and SNP-induced EIR. In LPS-treated mesenteric artery, L-arginine-induced relaxation was not affected by removal of endothelium, indicating muscular inducible nitric oxide synthase (iNOS) induction. Pre-exposure to SNP (NO donor) also moderately reduced ACh-induced EDR and markedly reduced SNP-induced EIR with little effect on ACh-induced EDHF-mediated EDR. In conclusion, in vitro exposure to LPS desensitized vascular smooth muscle cells to endogenous and exogenous NO by overproduction of muscular iNOS-derived NO, and an iNOS inhibitor and iNOS induction inhibitors prevented the LPS-induced desensitization.
Keywords: Acetylcholine; Endothelium; Endotoxin; iNOS; Mesenteric artery; Nitric oxide; Rat